2023
DOI: 10.1093/jisesa/iead012
|View full text |Cite
|
Sign up to set email alerts
|

Predation and parasitism of naturally occurring and sentinel stink bug egg masses ofHalyomorpha halys(Stål) andNezara viridula(L.) (Hemiptera: Pentatomidae) in various southeastern habitats

Abstract: Stink bugs, including Halyomorpha halys (Stål) and Nezara viridula (L.), are agricultural pests that feed on fruit in a variety of crops. Monitoring predation and parasitism of stink bug egg masses furthers our understanding of potential biological control tactics. However, best practices for laboratory and field assessments of parasitism and predation of egg masses require further attention. We carried out a series of laboratory and field experiments to test whether parasitism and predation for three types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Host suitability may also play a role; although Te. podisi can successfully develop in natural H. halys egg masses, as observed here, it often fails to complete development in this host (Cornelius et al 2016b, Ogburn et al 2016, Dieckhoff et al 2017, Tillman et al 2023).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Host suitability may also play a role; although Te. podisi can successfully develop in natural H. halys egg masses, as observed here, it often fails to complete development in this host (Cornelius et al 2016b, Ogburn et al 2016, Dieckhoff et al 2017, Tillman et al 2023).…”
Section: Discussionsupporting
confidence: 60%
“…2020). Unlike some previous studies, parasitism and predation of stink bug egg masses in crops in our study were assessed solely from naturally laid egg masses of H. halys and indigenous stink bug species existing together in an agroecosystem, for an earlier study at this site revealed that H. halys and N. viridula natural egg masses can have higher parasitism and lower predation compared to sentinel egg masses in soybean (Tillman et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations